CD2 Is a Novel Immune-Related Prognostic Biomarker of Invasive Breast Carcinoma That Modulates the Tumor Microenvironment - Chen, Yanzhu; Meng, Zhishang; Zhang, Lin; Liu, Feng (Frontiers in Immunology, 2021)
Female breast cancer is the most commonly occurring cancer worldwide. Tumor microenvironment (TME) plays an essential role in tumor invasion, angiogenesis, unlimited reproduction, and even immune escape, but we know little about TME of breast invasive carcinoma (BRCA). Here, we aimed to find a prognostic biomarker for BRCA, which could predict the prognosis and immunotherapy efficacy via TME. Based on the transcriptome RNA-seq data and clinical characteristics of 1222 cases obtained from the TCGA database, we used ESTIMATE algorithm to identify ImmuneScore and StromalScore and then screen out differentially expressed genes (DEGs). Afterwards, the protein-protein interaction (PPI) network and univariate COX regression were constructed to identify potential key genes. Five candidate genes were screened out, including CD2, CCL19, CD52, CD3E and ITK. We found that the CD2 expression level was associated with tumor size to some extent, but independent of TNM stage, lymph node status and distant metastasis. Correspondingly, GSEA analysis showed the significant pathways associated with high CD2 expression enriched in immune-related KEGG pathways. Our data indicate that the CD2 correlated with 16 types of tumor-infiltrating immune cells (TICs). Hence, CD2 might be a novel candidate-indicator in terms of molecular typing, and as a complementary means of TNM staging to improve clinical outcomes prediction of BRCA.